2014
DOI: 10.1038/cdd.2014.8
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt signalling activates TAZ through PP1A during osteogenic differentiation

Abstract: TAZ, a transcriptional modulator, has a key role in cell proliferation, differentiation and stem cell self-renewal. TAZ activity is regulated by several signalling pathways, including Hippo, GPCR and Wnt signalling, but the regulatory mechanisms of TAZ activation are not yet clearly understood. In this report, we show that TAZ is regulated by canonical Wnt signalling during osteogenic differentiation. Wnt3a increases TAZ expression and an inhibitor of GSK3b, a downstream effector of Wnt signalling, induces TAZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 47 publications
3
78
1
Order By: Relevance
“…Notably, recent unbiased proteomic studies have not identified the destruction complex as YAP/TAZ interacting proteins while these studies have validated many known YAP/TAZ binding partners (Couzens et al, 2013; Kohli et al, 2014; Kwon et al, 2013; Wang et al, 2014). Consistent with our results, Byun et al also showed that Wnt3a activates TAZ by dephosphorylating Lats1/2 target sites, demonstrating the link between Wnt3a and Hippo pathway (Byun et al, 2014). …”
Section: Discussionsupporting
confidence: 92%
“…Notably, recent unbiased proteomic studies have not identified the destruction complex as YAP/TAZ interacting proteins while these studies have validated many known YAP/TAZ binding partners (Couzens et al, 2013; Kohli et al, 2014; Kwon et al, 2013; Wang et al, 2014). Consistent with our results, Byun et al also showed that Wnt3a activates TAZ by dephosphorylating Lats1/2 target sites, demonstrating the link between Wnt3a and Hippo pathway (Byun et al, 2014). …”
Section: Discussionsupporting
confidence: 92%
“…TAZ activity is tightly regulated to maintain development and homeostasis because TAZ regulates the proliferation, differentiation, adhesion, and apoptosis of diverse cell types (50,51). Interestingly, TAZ phosphorylation on Ser-89 by the Hippo pathway kinase LATS promotes formation of a complex between TAZ and 14-3-3 that retains TAZ in the cytoplasm (20,26,52). Thus, LATS kinase inhibitor drugs, currently under development (35, 49 -51, 53) or natural compounds (54) shown to promote dephosphorylation of TAZ may, like HDACi, be useful for AML combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…8C). In these experiments, TAZ in the nuclear fraction consisted of multiple bands, likely reflecting posttranslational modifications, including phosphorylation at multiple residues, which occurs within the nucleus (20,26,35). As shown below (see Fig.…”
Section: Pp1␣-t320a Overexpression Saha Pretreatment or Upregulatiomentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, activated Wnt signaling through treatment with Wnt3a induces TAZ expression and increases its nuclear localization to stimulate osteogenic differentiation 36 . Activated mTOR signaling promotes expression of the transcription factor RUNX2 to induce osteogenesis 37 .…”
Section: Discussionmentioning
confidence: 99%